Palynological record of the Paleogene Río Leona Formation (southernmost South America): Stratigraphical and paleoenvironmental implications - Barreda, Viviana Dora (2009)
Terrestrial palynomorph assemblages have been recovered from the Río Leona Formation, southwestern Santa Cruz Province, southern South America. Organic debris (spores, pollen grains, fresh water algae, plant tissues and fungi) are preserved in shales associated with other plant fossil remains (leaves and wood). The Río Leona Formation is here assigned to the early Late Oligocene based on the presence of key species of the M–M palynological zone (Margocolporites tenuireticulatus Barreda, Diporites aspis Pocknall and Mildenhall, Granodiporites nebulosus Partridge, Mutisiapollis spp.) and the virtual absence of warmth-adapted taxa (abundant from the latest Late Oligocene to Middle Miocene in Patagonia). A temporal gap between the Río Leona Formation and the overlying Centinela Formation (Early Miocene) – exposed in the studied region – is suggested here based on the differences observed in their palynological assemblages. The Río Leona Formation was deposited in a continental environment, with local peat swamps and coastal plain environments. The presence of Antarctic lineages in the lower and middle sections of the Río Leona Formation is consistent with the cooling trend globally recognized during the Late Eocene and Early Oligocene times. The appearance of some Neotropical families in the upper section might indicate the beginning of the Late Oligocene warming event. Records of Asteraceae (Mutisiapollis telleriae Barreda and Palazzesi sp. nov.), Menyanthaceae (Striasyncolpites laxus Mildenhall and Pocknall), and Rosaceae (Psilatricolporites quenua Barreda and Palazzesi sp. nov., Psilatricolporites sp.) are the oldest reports in Patagonia to date, and provide significant information on the early divergence and radiation times of these major angiosperm families.